2014
DOI: 10.1039/c4cc03268c
|View full text |Cite
|
Sign up to set email alerts
|

A super water-stable europium–organic framework: guests inducing low-humidity proton conduction and sensing of metal ions

Abstract: The ordered dimethylammonium cations [H2N(CH3)2](+) and helical water spirals as guest species make a super water stable europium-organic framework possess a proton conductivity of over 10(-3) S cm(-1) at 68% relative humidity. A fluorescent probe for Fe(3+) and Cu(2+) ions via a different mechanism has also been realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(63 citation statements)
references
References 53 publications
1
62
0
Order By: Relevance
“…However, these quenched films can recover most of its original luminescence back via treated with Na 2 EDTA weak solution (see SI for details). These results suggested that partial ion-exchange might occur in the framework according to previously reported literatures [12,13].…”
Section: The Possible Mechanism Of Luminescence Quenchingsupporting
confidence: 60%
See 2 more Smart Citations
“…However, these quenched films can recover most of its original luminescence back via treated with Na 2 EDTA weak solution (see SI for details). These results suggested that partial ion-exchange might occur in the framework according to previously reported literatures [12,13].…”
Section: The Possible Mechanism Of Luminescence Quenchingsupporting
confidence: 60%
“…However, most MOFs are unstable in water, which strictly limited their sensing application in practical case [12]. The stability of Tb-SA films were investigated via time-dependent luminescence intensity analysis of strongest 5 D 4 → 7 F 5 emission at 545nm for 30 minutes, as illustrated in Fig.4.…”
Section: Characterization Of Tb-sa Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…The quenching on fluorescent MOFs by metal ions can be mainly caused by (1) the MOF structure being collapsed by the metal ion inbreak; (2) ion exchange occurrence between the metal nodes and the incoming cations; and (3) strong interaction between incoming metal ions and luminophores in the MOFs . In this case, to gain insights into the fluorescence sensing mechanism of Sc 2 (NH 2 ‐BDC) 3 in the selective detection of Ni 2+ and Co 2+ ions from molecule level, XPS, FTIR, EPR and ssNMR are utilized to reveal the interaction between the framework of Sc 2 (NH 2 ‐BDC) 3 and Ni 2+ /Co 2+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…Metal-multicarboxylate CPs not only possess the rich structures [6][7][8][9][10], many interesting physical properties have also been investigated [11][12][13][14][15][16][17][18][19][20]. For example, (i) porous metal-multicarboxylate CPs can selectively adsorb gases, in particular H 2 (for energy storage) and CO 2 (for purification of the environment) [21][22][23][24][25]; (ii) Zn 2+ /Cd 2+ /Ln 3+ -multicarboxylate CPs can emit light.…”
Section: Introductionmentioning
confidence: 99%